The Potential Role of Gymnema inodorum Leaf Extract Treatment in Hematological Parameters in Mice Infected with Plasmodium berghei - Sakaewan Ounjaijean; Suriyan Sukati; Voravuth Somsak; Orawan Sarakul (Journal of Tropical Medicine)
Malaria remains a significant cause of death in tropical and subtropical regions by serious complications with hematological abnormalities consistent with high parasitemia. Hence, this study aimed to determine the efficacy of the Gymnema inodorum leaf extract (GIE) on hematological alteration in Plasmodium berghei infection in mice. Groups of ICR mice were infected intraperitoneally with parasitized red blood cells of P. berghei ANKA (PbANKA). They were administered orally by gavage of 100, 250, and 500 mg/kg of GIE for 4 consecutive days. Healthy and untreated groups were given distilled water, while 10 mg/kg of chloroquine was treated as the positive control. Hematological parameters including RBC count, hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean cell hemoglobin (MCH), mean cell hemoglobin concentration (MCHC), RBC distribution width (RDW), white blood cell (WBC) count, and WBC differential count were measured. The results showed that significant decreases of RBC count, Hb, Hct, MCV, MCH, MCHC, and reticulocytes were observed in the untreated group, while RDW was significantly increased compared with the healthy control. Furthermore, the WBC, neutrophil, monocyte, basophil, and eosinophil of untreated mice increased significantly, while the lymphocyte was significantly decreased compared with the healthy control. Interestingly, GIE normalized the hematological alteration induced by PbANKA infection in GIE-treated groups compared with healthy and untreated groups. The highest efficacy of GIE was observed at a dose of 500 mg/kg. Our results confirmed that GIE presented the potential role in the treatment of hematological alteration during malaria infection.